Liberdade, cidadania e política de emancipação escrava - Cano, Jefferson (Revista de História, 1997)
This article analyses the political role of Campinas' planters in the process of the Brazilian slave emancipation. It suggests that the action of those slaveowners in the 1870's, trying to preserve the slave labour force, might be understood within a wider political project - the liberal one, which guided the making of the imperial State.